Diphenyl diselenide protects motor neurons through inhibition of microglia-mediated inflammatory injury in amyotrophic lateral sclerosis. (March 2021) - Zhang, Chunting; Wang, Hongyong; Liang, Weiwei; Yang, Yueqing; Cong, Chaohua; Wang, Ying; Wang, Shuyu; Wang, Xudong; Wang, Di; Huo, Di; Feng, Honglin
Graphical abstract: Highlights: DPDS exerts neuroprotective effects in ALS models via inhibiting proinflammatory M1 microglia-mediated neuroinflammation. DPDS inhibits the activation of IκB/NF-κB pathway and the release of neurotoxic factors from activated ALS microglia. DPDS suppresses NLRP3 inflammasome activation via reducing protein nitration in activated ALS microglia. Abstract: Microglia-mediated neuroinflammatory response and neuron damage are considered as a self-propelling progressive cycle, being strongly implicated in the progression of neurodegeneration in amyotrophic lateral sclerosis (ALS). Diphenyl diselenide (DPDS), a simple organoselenium compound, has been known to possess multiple pharmacological properties. The purpose of this study was to explore the neuroprotective effects of DPDS against microglia-mediated neuroinflammatory injury in ALS models. We found that DPDS pretreatment inhibited LPS-induced activation of IκB/NF-κB pathway and subsequent release of proinflammatory factors from activated primary hSOD1 G93A microglia. Moreover, DPDS suppressed NLRP3 inflammasome activation by decreasing protein nitration via reduction in NO and ROS levels, whose low levels are related to NF-κB inhibition responsible for iNOS and NOX2 down-regulations, respectively. Notably, DPDS-mediated ROS attenuation was not linked to Nrf2 activation in this cellular model. Furthermore, in the absence of activated microglia, DPDS has no significant effect on the individual hSOD1 G93A -NSC34 cells; however, in in vitro neuron-microglia conditional culture and co-culture experiments, DPDS protected motor neurons from neurotoxic damage caused by LPS or BzATP-stimulated microglia activation. Above observations suggest that DPDS-afforded neuroprotection is linked to inhibition of microglia-mediated neuroinflammation in ALS, which was further verified in vivo as shown by improvements of motor deficits, prolonged survival, and reduction of motor neuron loss and reactive microgliosis in hSOD1 G93A transgenic mouse. Altogether, our results show that DPDS elicited neuroprotection in ALS models through inactivation of microglia by inhibiting IκB/NF-κB pathway and NLRP3 inflammasome activation, suggesting that DPDS may be a promising candidate for potential therapy for ALS.